2016
DOI: 10.1038/srep30013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MMP1 as a novel risk factor for intracranial aneurysms in ADPKD using iPSC models

Abstract: Cardiovascular complications are the leading cause of death in autosomal dominant polycystic kidney disease (ADPKD), and intracranial aneurysm (ICA) causing subarachnoid hemorrhage is among the most serious complications. The diagnostic and therapeutic strategies for ICAs in ADPKD have not been fully established. We here generated induced pluripotent stem cells (iPSCs) from seven ADPKD patients, including four with ICAs. The vascular cells differentiated from ADPKD-iPSCs showed altered Ca2+ entry and gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…They found that the expression level of a metalloenzyme gene, matric metaloproteinase (MMP)-1 was specifically elevated in hiPSC-derived endothelial cells from ADPKD patients with aneurysms. In addition, they confirmed a positive correlation between serum MMP1 levels and the development of intracranial aneurysms in 354 ADPKD patients, indicating that high serum MMP1 levels might constitute a novel risk factor for ADPKD [146]. …”
Section: Disease Modeling Using Kidney Organoidsmentioning
confidence: 94%
See 2 more Smart Citations
“…They found that the expression level of a metalloenzyme gene, matric metaloproteinase (MMP)-1 was specifically elevated in hiPSC-derived endothelial cells from ADPKD patients with aneurysms. In addition, they confirmed a positive correlation between serum MMP1 levels and the development of intracranial aneurysms in 354 ADPKD patients, indicating that high serum MMP1 levels might constitute a novel risk factor for ADPKD [146]. …”
Section: Disease Modeling Using Kidney Organoidsmentioning
confidence: 94%
“…This phenomenon might help explain the cause for cystogenesis in ADPKD patients; yet, further studies are required to elucidate the mechanisms of cystogenesis due to reduced PKD2 expression in the cilium and furthermore, on how this relates to why it takes a number of decades to form cysts in ADPKD patients. Another recent study on ADPKD using patient-derived hiPSCs attempted to explore risk factors for intracranial aneurysms [146]. The authors established hiPSCs from three ADPKD patients without intracranial aneurysms and four patients with aneurysms, and compared gene expression profiles between those two groups after hiPSC differentiation into endothelial cells.…”
Section: Disease Modeling Using Kidney Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, iPSCs cells have been established from ADPKD patients heterozygous for a PKD1 mutation . Since these iPSCs were derived from fibroblasts, somatic mutations that might have contributed to cystogenesis will be missed.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with polycystic kidney disease (PKD), serum MMP-1 concentrations were elevated compared to the controls [33]. Serum MMP-1 levels were found to be significantly increased in the induced pluripotent stem cell-derived endothelial cells from patients with ADPKD and intracranial aneurysms [34]. …”
Section: Collagenases (Mmp-1 Mmp-8 Mmp-13 and Mmp-18)mentioning
confidence: 99%